Evaluation of tolerance and efficacy of palliative irinotecan chemotherapy in patients with colorectal cancer - Utracka-Hutka, Beata; Nowara, Elżbieta; Słomian, Grzegorz; Suwiński, Rafał (Contemporary Oncology/Współczesna Onkologia, 2003)
More than a half of colorectal cancer patients experience distant metastases, especially to the liver. 5-Fluorouracil based therapy modulated with folinic acid is the standard chemotherapy. Selected patients can be treated with second line chemotherapy based on the drugs with no cross-resistance with fluorouracil when they relapse. We present a group of 37 patients with metastatic colorectal cancer and analyze the efficacy of second line mono- or poli-chemotherapy based on irinotecan. Thirty four patients received irinotecan alone, and three combined with 5-fluorouracil. There were given 1 to 9 cycles, median 4.5. The response rate was 48.6% (18 pts) with partial remission 19% (7 pts). The median duration of response was 13.6 weeks (2-27 weeks). Four patients experienced progression after the first cycle. We did not observe any serious adverse events, discontinuation of treatment was not caused by SAE in any case. The most common adverse event was diarrhea – 10 pts (27%), but only one patient experienced grade 3 WHO, and fatigue – 5 pts (13.5%). We conclude that second line chemotherapy can be useful in a selected group of patients with metastatic colorectal cancer.